2021
DOI: 10.2174/1389201021666201208115525
|View full text |Cite
|
Sign up to set email alerts
|

Is Hospital Autopsy Auditing Suitable for Clinical Risk Manage ment? Actualities and Perspectives of Auditing in the Autopsy Room Following Italian Law 24/2017 on Patient Safety

Abstract: Background: Autopsies are a valuable tool for understanding the physiopathology of a disease and it is the gold standard to assess the cause of death. The clinical autopsy is the ultimate medical service for a patient and plays a crucial role in the context of quality control, education of physicians and other medical personnel, as well as mitigation of risk of malpractice claims. Objective: This study aims to demonstrate the importance of improving an autopsy service and the relevance of this investigation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…An improved physician/medical system-patient relationship is therefore necessary to reduce the number of disputes, with the additional benefits of lowering daily medical practice stress levels and likely enhancing the overall performance. Even if during the last two decades the total number of malpractice claims has decreased, the payout per claim has increased significantly, especially in tragic cases where the patient deceased during or immediately after the procedure [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An improved physician/medical system-patient relationship is therefore necessary to reduce the number of disputes, with the additional benefits of lowering daily medical practice stress levels and likely enhancing the overall performance. Even if during the last two decades the total number of malpractice claims has decreased, the payout per claim has increased significantly, especially in tragic cases where the patient deceased during or immediately after the procedure [7].…”
Section: Discussionmentioning
confidence: 99%
“…When fatalities occur after neurosurgery and FES is suspected, a complete post mortem investigation should be considered mandatory to disclose the causes of the unexpected deaths, to promote a policy of transparency and to prevent legal claims [7]. On 8 march 2017 Italy enacted the law no.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Mordeglia et al that counted 560 autopsy examinations of patients with PE demonstrated that the prevalence of PI was 60%, which represent a very high number [ 9 ]. Therefore, when the death occurs unexpectedly or PE is suspected, an autopsy should be considered mandatory to investigate the PI [ 5 ].…”
Section: Epidemiologymentioning
confidence: 99%
“…Very often misdiagnosis or delayed diagnosis of PE results in difficult identification of PI [ 2 , 3 ]. Furthermore, the short- and long-term consequences after PE that can lead to PI and a higher risk of death are still unclear [ 1 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%